Various Non-Injectable Delivery Systems for the Treatment of Diabetes Mellitus - Yadav, Neha; Morris, Gordon; Harding, S. E.; Ang, Shirley; Adams, G. G. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2009)
Diabetes mellitus (diabetes) is suffered by more than 180 million people and is responsible for approximately 2.9 million deaths each year. This mortality rate is expected to increase by 50 % in the next decade. Due to the inconvenience of the traditional treatment of diabetes by subcutaneous administration of insulin injection, various attempts are made in the production, purification, formulation and methods of delivery of insulin. However, despite advances in recent years, these attempts have met with limited success. Various alternative routes such as rectal, ocular, nasal, pulmonary and oral have been exploited. The pulmonary route offers great potential for the delivery of polypeptide drugs due to the large surface area for insulin absorption in the respiratory tract. But due to its low bioavailability, oral route is intensely investigated for the insulin delivery. Microencapsulation, as one of the delivery systems utilising oral route, has shown some potential progress in insulin delivery; though it is at an early stage yet it has proved to be quite encouraging providing new less toxic immunosuppressive agents. Microencapsulation may prove to be an attractive delivery system for controlled release of insulin and beneficial for therapeutic, bio-efficient and bio-effective drug delivery. In this review we discuss the possible alternative routes for insulin delivery (ocular, nasal, pulmonary and oral) and advantages and disadvantages of each. Furthermore we consider the different drug delivery strategies available (aerosols, dry powder inhalers, synthetic beta cells, hydrogels and microcapsules) and their current and potential applications with respect to the different insulin delivery routes.
Keywords: microcapsules